2012
DOI: 10.1063/1.4753936
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic effects of ultra-thin Mo films on hydrogenated amorphous Si photovoltaic cells

Abstract: We report on the improvement of short circuit current (JSC), fill factor (FF), and open circuit resistance (ROC) in hydrogenated amorphous silicon (a-Si:H) photovoltaic cells with a p-type/intrinsic/n-type structure, \ud achieved by the addition of an ultra-thin molybdenum film between the p-type film and the transparent conductive oxide/glass substrate. \ud For suitable conditions,improvements of ~10% in average internal quantum efficiency and up to 5%–10% under standard\ud illumination in JSC, FF, and ROC ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…To test such concept we have performed reverse bias stress experiments in samples in which the TCO layer in contact with the p-type a-Si: H film has been replaced by a Mo film, in cells realized as described in the previous section. The use of Mo can give some advantage for the p-type a-Si:H/metal contact resistance and for the solar cell carrier lifetime (compared to FTO) [10,11], and it may be advantageous to fabricate a-Si:H solar cells on flexible substrates [12], and to realise plasmonic light trapping [21]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test such concept we have performed reverse bias stress experiments in samples in which the TCO layer in contact with the p-type a-Si: H film has been replaced by a Mo film, in cells realized as described in the previous section. The use of Mo can give some advantage for the p-type a-Si:H/metal contact resistance and for the solar cell carrier lifetime (compared to FTO) [10,11], and it may be advantageous to fabricate a-Si:H solar cells on flexible substrates [12], and to realise plasmonic light trapping [21]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that in the case of Mo, the SPP modes at the metal amorphous/silicon (A-Si:H) interface are at wavelengths higher than ≈500 nm, respectively. This results in a longer SPP lateral propagation, and therefore the SPP waves can reach the side contacts of the structure without undergoing excessive attenuation [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Basics Of Spps Propagation and Problem Formulation For A Mul...mentioning
confidence: 99%
“…We have demonstrated that the barrier height at the interface between Mo/p-type a-Si:H is 20 meV lower than that of SnO 2 :F/p-type a-Si:H and that the V oc of the Mo solar cell is 100 mV greater than that obtained with SnO 2 :F as front contact (Foti et al, 2011). Moreover, in Lombardo et al (2012) we have shown that the addition of an ultra-thin molybdenum film between the p-type a-Si:H film and the TCO/glass substrate in p-i-n a-Si:H solar cells causes an improvement of 10% in the internal quantum efficiency, due to the excitation of surface plasmon polariton modes at the a-Si:H/Mo interface.…”
Section: Introductionmentioning
confidence: 98%